Case Report: 18F-FDG PET-CT for Diagnosing Prosthetic Device-Related Infection in an Infant With CHD - Kawamura, Junpei; Ueno, Kentaro; Taimura, Eri; Matsuba, Tomoyuki; Imoto, Yutaka; Jinguji, Megumi; Kawano, Yoshifumi (Frontiers in Pediatrics, 2021)
Patients who have undergone cardiac surgery using prosthetic devices have an increased risk of developing prosthetic device-related infection and mediastinitis. However, accurate diagnosis of prosthetic device-related infection can be difficult to evaluate and treat with antibiotic therapy alone. In recent years, 18F-fluorodeoxyglucose positron emission tomography-computed tomography (18F-FDG PET-CT) has made promising contributions to detect infective endocarditis, pacemaker infections or other inflammations. Nevertheless, 18F-FDG PET-CT for congenital heart disease (CHD) with device infection has been sparsely reported. We report an infantile girl diagnosed with pulmonary atresia with ventricular septal defect and underwent replacement of the right ventricle to pulmonary artery (RV-PA) conduit for improvement cyanosis. She developed high fever and was diagnosed with mediastinitis and bacteremia by Pseudomonas aeruginosa (P. aeruginosa) on postoperative day 4. Mediastinal drainage and 6 weeks of antibiotic therapy improved her condition, but bacteremia flared up on postoperative day 56. Despite a long course of antibiotic therapy, she had two more recurrences of bacteremia with the detection of P. aeruginosa. Echocardiography and chest contrast CT showed no evidence of vegetation and mediastinitis. On postoperative day 115, 18F-FDG PET-CT revealed an accumulation on the RV-PA conduit (SUV max 3.4). Finally, she developed an infectious ventricular pseudo-aneurysm on postoperative day 129 and underwent aneurysm removal and RV-PA conduit replacement on postoperative day 136. Our case showed the importance of 18F-FDG PET-CT for diagnosing specific localization of prosthetic device-related infection that is hard to detect on other imaging techniques. It can be a useful diagnostic tool for infantile patients with CHD with cardiac prosthetic devices and improve subsequent clinical treatments.